Netralitas Pegawai Negri Sipil (PNS) Dalam Pemilu Menurut Undang-Undang Nomor 10 Tahun 2008 - I Made Mandi Widhiana (Universitas Mahendradatta, 2018)
In the legal and governmental aspects, civil servant bureaucracy reform is a very strong issue to be realized. This is because the Indonesian government bureaucracy is suspected to have contributed greatly to the occurrence of these various crises. By using the method of normative legal research a research method that discusses tie the norm angle in legal material. Furthermore, some of the problems that will be studied are 1) about the neutrality of civil servants in the General Election and 2) how to ensure the neutrality of civil servants themselves. By using a number of state legal theories, constitutional theories and legislative theories and theories of authority, and using the normative legal theory it will obtain discussion as follows:The bureaucracy built by the New Order government has fostered a bureaucratic culture that is thick with corruption, collusion and nepotism (KKN),Therefore bureaucratic reform is expected to be a corrective step towards the Government's political policy after the New Order.The conclusions obtained are: 1) the neutrality of civil servants in the reform of the bureaucracy, the Government has established new policies in coaching Civil Servants (PNS) as part of coaching 2) efforts to guarantee the neutrality of civil servants carried out with socialization and approach approach to the ceremony